A Synthetic Small RNA Homologous to the D-Loop Transcript of mtDNA Enhances Mitochondrial Bioenergetics - Mathuram, Theodore L.; Townsend, Danyelle M.; Lynch, Vincent J.; Bederman, Ilya; Ye, Zhi-Wei; Zhang, Jie; Sigurdson, Wade J.; Prendergast, Erin; Jobava, Raul; Ferruzza, Jonathan P.; D’Angelo, Mary R.; Hatzoglou, Maria; et al. (Frontiers in Physiology, 2022)
Mitochondrial malfunction is a hallmark of many diseases, including neurodegenerative disorders, cardiovascular and lung diseases, and cancers. We previously found that alveolar progenitor cells, which are more resistant to cigarette smoke-induced injury than the other cells of the lung parenchyma, upregulate the mtDNA-encoded small non-coding RNA mito-ncR-805 after exposure to smoke. The mito-ncR-805 acts as a retrograde signal between the mitochondria and the nucleus. Here, we identified a region of mito-ncR-805 that is conserved in the mammalian mitochondrial genomes and generated shorter versions of mouse and human transcripts (mmu-CR805 and hsa-LDL1, respectively), which differ in a few nucleotides and which we refer to as the “functional bit”. Overexpression of mouse and human functional bits in either the mouse or the human lung epithelial cells led to an increase in the activity of the Krebs cycle and oxidative phosphorylation, stabilized the mitochondrial potential, conferred faster cell division, and lowered the levels of proapoptotic pseudokinase, TRIB3. Both oligos, mmu-CR805 and hsa-LDL1 conferred cross-species beneficial effects. Our data indicate a high degree of evolutionary conservation of retrograde signaling via a functional bit of the D-loop transcript, mito-ncR-805, in the mammals. This emphasizes the importance of the pathway and suggests a potential to develop this functional bit into a therapeutic agent that enhances mitochondrial bioenergetics.